2001
DOI: 10.1096/fj.01-0183com
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myosin structure and function in response to glycation

Abstract: Nonenzymatic glycosylation (glycation) is recognized as an important post-translational modification underlying alterations of structure and function of extracellular proteins. The effect of glycation on intracellular proteins is, on the other hand, less well known despite the vital importance of intracellular proteins for cell, tissue, and organ function. The aim of this study was to explore the effects of glycation on the structure and function of skeletal muscle myosin. Myosin was incubated for up to 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 42 publications
6
90
1
1
Order By: Relevance
“…The present results are consistent with the previous findings that RA exerts a beneficial effect in preventing cardiac remodeling, including the extracellular matrix (ECM), and fibrosis (9,10). Cardiac hypertrophy has been shown to be associated with increased expression of ␤-MHC and ␣-SKA (53,54). The present results suggest that an increased expression of hypertrophic marker genes such as ␤-MHC and ␣-SKA in the heart of Npr1 ϩ/Ϫ mice contributed to the development of cardiac hypertrophy in these animals.…”
Section: Discussionsupporting
confidence: 93%
“…The present results are consistent with the previous findings that RA exerts a beneficial effect in preventing cardiac remodeling, including the extracellular matrix (ECM), and fibrosis (9,10). Cardiac hypertrophy has been shown to be associated with increased expression of ␤-MHC and ␣-SKA (53,54). The present results suggest that an increased expression of hypertrophic marker genes such as ␤-MHC and ␣-SKA in the heart of Npr1 ϩ/Ϫ mice contributed to the development of cardiac hypertrophy in these animals.…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that these changes are the result of physiological alterations to skeletal muscle before measureable sensory neuropathy is observed. Nonenzymatic glycation as a result of diabetes may affect the contractile machinery of skeletal muscle independently of neuropathy as shown previously on isolated animal muscle (27). This may at least party explain why changes have been observed proximally at the knee extensors as well as distally at the ankle extensors in diabetic patients without neuropathy.…”
Section: Discussionsupporting
confidence: 64%
“…We favor the proposal that ADP release is the rate-limiting factor and may be altered with age because we have previously shown that during a maximal isometric contraction there is an increase in the apparent rate constant for myosin detachment from actin with age (Lowe et al, 2002), and ADP release is the critical step controlling detachment. Furthermore, it has been suggested that a structural alteration in the catalytic domain of MHC causes the age-related contractile deficits (Lowe et al, 2001;Lowe et al, 2002;Ramamurthy et al, 2001). A similar proposal has been suggested to explain sarcoplasmic reticulum Ca 2+ -ATPase functional alterations that occur with age (Chen et al, 1999;Ferrington et al, 1997).…”
Section: Discussionmentioning
confidence: 85%